EKSEKUSI HUKUMAN MATI DI INDONESIA (TINJAUAN HUKUM PIDANA ISLAM) - NURWAHIDAH NURWAHIDAH (Universitas Islam Negeri Antasari Banjarmasin, 2014)
The death penalty is still carried out in many countries, including Indonesia. Considering the death penalty concerning human lives, then multiply the pros and cons of going on in the community, but the Indonesian government together with some elements of society who support the death penalty remains on the establishment, that the death penalty should still be implemented to protect life. This paper seeks to inform some of the death penalty that has been implemented for a variety of specific criminal acts. This paper seeks to criticize, the extent of execution cases it can be justified according to Islamic criminal law. The results of this paper show the majority of crimes are indeed subject to the death penalty, there are still containing the controversy, but some are actually able to be released from the death penalty because the victim's family in a murder case has been forgiven.